Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 39. Beitrag. Coleoptera: Chrysomelidae I (Halticinae). - Mohr, Karl-Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The present paper deals with the Halticinae of Albania. The study of the material of the expedition to Albania by Deutsches Entomologisches Institut and of other, smaller collections established 87 species of Halticinae in Albania. 28 species unknown in Albania until now were found. One new subspecies (Crepidodera femorata albanica ssp. geogr. nov.) is described. Nomenclatural Acts albanica Mohr, 1965 (Crepidodera femorata), sspec. n.